Influenceservice Qualityand Prices on Customer Satisfaction PT Alfamart Trijaya Tbk SM Raja 3 Pematang Siantar - Butar-Butar, Diana Florenta; Panjaitan, Hadi; Sitanggang, Augustinus Suryadi; Barus, Ben Setiawan; Nainggolan, Anju Bherna D. (ProBisnis : Jurnal Manajemen, 2023)
This research is motivated by the large number of Alfamarts so the author is interested in finding out about the influence of service quality and price on customer satisfaction at Alfamart Sm Raja 3 Pematang Siantar. However, each person has a different point of view in assessing the service they experience and the customer satisfaction they receive. The level of customer satisfaction really depends on the quality of a product, whether in the form of goods or services they consume. One of them is at Alfamart Sm Raja 3 Pematang Siantar. The aim of this research is to determine the effect of service quality on customer satisfaction at Alfamart Sm Raja 3 Pematang Siantar. This type of research is field research, while the nature of this research is quantitative research. The population of this research is all customers of Alfamart Sm Raja 3 Pematang Siantar. The population used is unlimited. In this study, the sample required for this research was 50 respondents.